On the nonlinear theory of gas wells - Polyakov, V.L. (Reports of the National Academy of Sciences of Ukraine, 2017)
The effect of a single gas well in a head seam is considered in view of a fluid and the rock compressibility. A mathematical task of the fluid pumping with constant discharge is formulated and solved in nonlinear and linear statements by analytical methods for two stages of the underground flow process. On numerous examples, the analysis of the disturbance zone expansion and the bottom pressure decrease is conducted. Errors due to different ways of the nonlinear task linearization are evaluated.